Pemahaman Masyarakat Tentang Mengambil Sejengkal Tanah Di Desa Pagar Agung Kecamatan Pseksu Kabupaten Lahat Dengan Paradigma Hadis - Mahmud, Lenya Emilia; Mugiyono, Mugiyono; Almunadi, Almunadi (el-Sunnah: Jurnal Kajian Hadis dan Integrasi Ilmu, 2023)
This research is entitled "Community's Understanding About Taking anInch of Land in Pagar Agung Village, Pseksu District, Lahat Regency withthe Hadith Paradigm" The hadith of taking an inch of land is a hadith thatexplains the law for someone who commits unjust acts (land problems), such asthe hadith narrated by Shahih Bukhari, Rasulullah SAW said "whoever abuses apiece of land on this earth then later he will be burdened with land from sevenearths". But this hadith contradicts life in the community in Pagar Agung Village,Pseksu District, Lahat Regency. The problem is how the understanding of themuhadditsin scholars regarding the hadith of taking an inch of land and how theunderstanding of the people of Pagar Agung Village, Pseksu District, LahatRegency regarding the law of taking an inch of land is in accordance with thehadith of the Rasulullah Saw.This type of research uses field research, namely research that goes directlyto the location to make observations about a phenomenon that occurs in order toget answers to a problem. The type of data used is qualitative data and isdescriptive in nature. The data sources for this research are primary data sourcesand secondary data sources. Data collection techniques in this study were obtainedby observing, interviewing and documenting. Data analysis techniques carried outduring the research process used Scuthz's theory of action.The results of this study can be concluded that the muhaddittsin scholarsagree on the law of taking an inch of land, that is, on the day of the afterlife, it willbe worn with seven layers of earth and the understanding of the people in PagarAgung Village, Pseksu District, Lahat Regency is still lacking in the hadith abouttaking an inch of land. Some people do not know the hadith about taking an inchof land, while some people already know the hadiths about taking an inch of landand think that this hadith is very good because it reminds people about unjust actsand the punishment they will receive in the hereafter if the unjust acts arecommitted. In this study, there are various motives for someone deciding to takean inch of land, among others, because of past grudges and jealousy whensomeone else's land is larger than his own.